The Effect of Mindfulness Yoga in Children With School Refusal: A Study Protocol for an Exploratory, Cluster-Randomized, Open, Standard Care-Controlled, Multicenter Clinical Trial - Amitani, Marie; Amitani, Haruka; Owaki, Tetsuhiro; Monuki, Takako; Adachi, Satomi; Kawazu, Suguru; Fukumoto, Takamasa; Suzuki, Hajime; Yoshimura, Takuya; Mizuma, Kimiko; Nishida, Yuko; Watanabe, Hiroko; et al. (Frontiers in Public Health, 2022)
Background School refusal occurs in about 1–2% of young people. Anxiety and depression are considered to be the most common emotional difficulties for children who do not attend school. However, at present, no definitive treatment has been established for school refusal, although interventions such as cognitive behavioral therapy have been used. This paper reports a protocol for a cluster-randomized controlled trial of a mindfulness yoga intervention for children with school refusal. Methods This study is a multicenter, exploratory, open cluster-randomized controlled trial. This study will recruit children aged 10–15 years with school refusal. After a 2-week baseline, participants for each cluster will be randomly assigned to one of two groups: with or without mindfulness yoga for 4 weeks. Mindfulness yoga will be created for schoolchildren for this protocol and distributed to the participants on DVD. The primary outcome is anxiety among children with school refusal using the Spence Children's Anxiety Scale-Children. Discussion For this study, we developed a mindfulness yoga program and protocol, and examine whether mindfulness yoga can improve anxiety in children with school refusal. Our mindfulness yoga program was developed based on the opinions of children of the same age, and is a program that children can continue to do every day without getting bored. In this way, we believe that we can contribute to the smooth implementation of support to reduce the anxiety of children with school refusal, and to the reduction of the number of children who refuse to go to school.